Ácido salicílico em sementes de feijoeiro: qualidade fisiológica e tolerância de plântulas ao estresse por baixa temperatura - Fernandes, Tiéle Stuker (2018)
The common bean when sown in august and september in Rio Grande do Sul is subject to damages and losses due to the low temperature stress common in this period. Thus, the germination and emergence of the seeds are impaired and the seedlings present reduced growth and development. The damage caused by stress can be minimized by the application of plant hormones. Salicylic acid acts in different physiological processes in plants, besides acting as a signal and inducer of tolerance to several abiotic stresses, such as drought, extreme temperatures, salinity and contamination by heavy metals. Thus, the application of salicylic acid may contribute to the tolerance of bean seedlings to low temperature stress during germination and initial development of the crop. Thus, the objective of this study was to study the application of different concentrations of salicylic acid and forms of application of the product in bean seeds; as well as the effect of salicylic acid on the germination and initial development of seedlings submitted to low temperature stress. Seed germination, growth, mass accumulation, antioxidant enzyme activity and lipid peroxidation of seedlings were evaluated. In the first chapter, the bean seeds of the cultivars Fepagro 26 and SCS204 Predileto were submitted to germination with the application of different concentrations of salicylic acid, being zero, 250, 500, 750, 1000, 3000 and 5000 μM. Seed imbibition occurred in two ways: [1] germination paper moistened with salicylic acid solutions; [2] imbibition of seeds in salicylic acid solutions in plastic boxes for 24 hours and subsequent sowing on germinated paper moistened with distilled water. The material was kept in a germination chamber under constant photoperiod and temperature of 25 ° C. On the fifth day after sowing the number of normal seedlings (first count), length, fresh and dry mass of seedlings were determined. The percentage of germination was evaluated nine days after sowing. It was concluded that the salicylic acid in concentrations up to 1000 μM did not affect the germination of bean seeds of the cultivars Fepagro 26 and SCS204 Predileto, using the soaking of the seeds for 24 hours and the imbibition in the paper of germination. Salicylic acid concentrations up to 1000 μM and soaking the seeds for 24 hours does not affect the vigor (first count) of the two bean cultivars. In the experiments of the second chapter the objective was to study the tolerance induced by salicylic acid in bean seeds in the germination and initial development of seedlings under low temperature stress, evaluating the physiological and biochemical parameters of the seedlings. The experiment developed to evaluate the physiological performance of the seeds was conducted in a 5 x 4 bipatorial, with concentrations of salicylic acid (zero, 250, 500, 750 and 1000 μM) and temperature regimes (25, 20, 15, 20-10 ºC), using seeds of the cultivars Fepagro 26 and SCS204 Predileto. The percentage of normal seedlings of the germination test (first count) was evaluated on the fifth day after sowing and the percentage of germination on the ninth day. On the seventh day the length, the fresh mass and the dry mass of the seedling were determined after drying in an oven for 48 hours. For the biochemical experiment, only seeds of the Fepagro 26 cultivar, conducted in a 4 x 3 bifactorial (zero, 250, 500 and 750 μM x 25, 15 and 20-10 ° C) were used, evaluated at seven days after sowing the activity of the enzymes superoxide dismutase, guaicol peroxidase and the lipid peroxidation of the bean seedlings. It is concluded that temperatures of 15ºC and 20-10ºC affect the germination and vigor of the bean seeds, but the cultivars Fepagro 26 and SCS204 Predileto show different behavior regarding low temperature stress. The exogenous salicylic acid induces the tolerance of bean seedlings to low temperature stress during germination and initial development, promoting greater germination and vigor of the seeds in the concentrations of 100 to 400 μM for the Fepagro 26 cultivar, and in the concentrations between 250 a 700 μM for the cultivar SCS204 Predileto. Salicylic acid induces the activation of the antioxidant enzyme guaiacol peroxidase in the primary root of bean seedlings of the Fepagro 26 cultivar under low temperature, but does not induce activation of the enzyme superoxide dismutase and does not reduce lipid peroxidation.